Experimental effects of early‐life corticosterone on the hypothalamic–pituitary–adrenal axis and pre‐migratory behaviour in a wild songbird. (19th December 2015) - Pakkala, Jesse J.; Norris, D. Ryan; Sedinger, James S.; Newman, Amy E. M.
Summary: Although laboratory studies have shown that chronic exposure to elevated glucocorticoids during development can have profound effects on the physiology and behaviour of animals, we still have a poor understanding of the proximate and ultimate consequences of early life stress on individuals in the wild. In an island population of Savannah sparrows ( Passerculus sandwichensis ), we examined multiple hypotheses to explain how elevated glucocorticoid exposure during the nestling period influenced both hypothalamic–pituitary–adrenal (HPA) axis function during the nestling period and the subsequent movement and survival of young after they fledged the nest. We exposed nestlings to exogenous corticosterone from 2 to 6 days of age and then measured both baseline and stress‐induced (30‐min restraint) plasma corticosterone levels prior to fledging (day 7). We then recaptured young throughout the pre‐migratory period and used mark–recapture analysis to estimate temporary emigration from the capture site (movement) and survival. Corticosterone‐treated nestlings had higher baseline corticosterone levels and lower stress reactivity than untreated individuals, and were more sensitive to inclement weather. Although there was no evidence that corticosterone treatments influenced survival, treated individuals had higher rates of temporary emigration outside of the study site than sham or controls. Our results provide support for the ceiling hypothesis, which suggests that individuals with chronic elevated glucocorticoids can lead to a dampened HPA axis response. We also provide support for the CORT‐activity hypothesis, which suggests that elevated glucocorticoids can increase activity levels, at least 1–2 months after leaving the nest. Our study highlights the importance of tracking individuals across multiple stages of the annual cycle to understand how early life events carry over to influence both physiology and behaviour. Abstract : Lay Summary